THE PROPHET’S EDUCATIONAL METHOD OF INDIRECT ADVICE: AN ANALYSIS OF ṢAḤĪḤ AL-BUKHĀRĪ NO. 6031 - Siti Asmaul Alif ALIF; Bmbang Tetuko Ponco Hernowo; Abdillah Afabih; Nabilah Qothrul Muna (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The development of social media in the modern era has significantly transformed patterns of communication within society. Sarcastic remarks, harsh comments, and degrading expressions are often regarded as forms of humor or freedom of expression, even though such phenomena may lead to verbal bullying and the deterioration of communication ethics. This condition reflects a shift in social values that contrasts sharply with the Prophet Muhammad’s model of communication, which emphasized gentleness, wisdom, and respect for human dignity. One example of the Prophet’s educational communication can be found in the hadith containing the expression “ترب جبينه,” which was used as a subtle form of admonition without hurting the feelings of others. Based on this phenomenon, this study aims to examine the authenticity of the hadith narrated by al-Bukhārī no. 6031 and to analyze the educational values embedded within it. This research employs a library research method using a descriptive qualitative approach. Data were collected from hadith compilations, hadith commentaries, and other relevant scholarly sources, then analyzed through sanad and matn criticism as well as a fiqh al-ḥadīth approach. The findings indicate that the hadith is classified as ṣaḥīḥ due to the support of multiple corroborating chains of transmission. The sanad is considered continuous, and most of the narrators are categorized as trustworthy (thiqah), although one narrator, Fulayḥ bin Sulaymān, remains disputed among scholars. Furthermore, the matn does not contradict the Qur’an or other authentic hadiths. This study concludes that the expression “ترب جبينه” does not represent an insult, but rather a form of ta‘rīḍ tarbawī that reflects the Prophet’s gentleness and ethical approach in educating his community.